Posterior-Chamber Phakic Intraocular Lens Implantation in Patients over 40 Years of Age - Pedro Tañá-Rivero; Francisco Pastor-Pascual; Marceliano Crespo; José L. Rodríguez-Prats; José J. Muñoz-Tomás; Robert Montés-Micó (Journal of Ophthalmology)
Purpose. To assess the efficacy, safety, and predictability of the Visian Implantable Collamer Lens (ICL) model having a central port in patients over 40 years of age. Methods. This study included 33 eyes from 21 patients who underwent V4c ICL implantation for the correction of myopia and myopic astigmatism. We assessed uncorrected (UDVA) and corrected (CDVA) distance visual acuity, refraction, intraocular pressure (IOP), endothelial cell density (ECD), vault, and adverse events occurring over a 1-year period. Results. Mean age of the patients at the time of implantation was 43.52 ± 4.49 years (range: 40 to 56 years). Efficacy and safety indexes were 1 and 1.09, respectively. Surgical outcomes for CDVA were as follows: no eye lost any lines, 19 eyes (57.58%) showed no CDVA changes, 7 eyes (21.21%) gained 1 line, 4 eyes (12.12%) gained 2 lines, and 3 eyes (9.09%) gained ≥3 lines. Mean postoperative spherical equivalent (SE) was −0.09 ± 0.47 D. A total of 29 eyes (87.8%) were within ±0.50 D and 31 eyes (93.9%) were within ±1.00 D of the desired SE. At 1-year, mean IOP was 15.27 ± 3.03 mmHg (range: 9 to 20 mmHg, p=0.12 pre vs. post) and mean ECD was 2516 ± 234 cells/mm2 (p=0.29 pre vs. post). Mean postoperative vault was 320 ± 136 μm, with 201–300 μm being the most prevalent vault range for 9 eyes (31.03%). None of the eyes showed a vault >701 μm. There were neither intraoperative nor postoperative complications; in fact, all ICL implantation procedures were uneventful. Conclusions. Our study’s findings support the use of this lens in patients over 40 years of age. A long follow-up period is advisable to monitor ICL position relative to the crystalline lens.